Evaluating the Environmental Kuznets Curve: The Role of Renewable Energy, Economic Growth, Urban Density and Trade Openness on CO2 Emissions. An Analysis for High-Income Countries Using the CS-ARDL Model - Vallejo Mata, Juan Pablo; González Bautista, María Gabriela; Solis Granda, Luis Eduardo; Zurita Moreano, Eduardo Germán (International Journal of Energy Economics and Policy, 2024)
In view of the environmental challenges the world is currently facing, the objective of this research was to examine the short- and long-term effect of renewable energies on CO2 emissions. In addition, to deepen the analysis, the Environmental Kuznet Curve (EKC) hypothesis, and the effects of urban population density and trade openness on CO2 emissions in 30 high-income countries in the period 2000-2020 were evaluated. A cross-sectional autoregressive distributed lags model (CS-ARDL) and the Augmented Mean Group (AMG) model were estimated for robustness checks. The findings reveal that renewable energy consumption reduces CO2 emissions in both the short and long term. Furthermore, there is strong evidence to support the EKC hypothesis. Finally, openness to trade was found to increase CO2 emissions, while the relationship between urban density and CO2 emissions is statistically non-significant. This information is expected to be crucial for the generation of public policies framed in sustainable development.